A century of curling, 1850-1950: an historical sketch of the Montreal Caledonia Curling Club, with a record of a century of sportsmanship - Montreal Caledonia Curling Club (Montreal Caledonia Curling Club, 1950)
Keywords: Clubs; Curling

The History of the Montreal Hunt 1826-1953 - Cooper, John Irwin (Montreal Hunt, 1953)
Keywords: Chasse à courre; Clubs; Montreal Hunt Club

Le réseau associatif de l'École littéraire de Montréal - Couture, François (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: École littéraire de Montréal; Écrivains

Histoire du vélo à Montréal-Nord - Gagné, Jean-François (Il était une fois...Montréal-Nord, 2024)
Keywords: Cyclisme; Montréal-Nord

Parcs et terrains de jeux à Montréal-Nord [1] - Lord, Claude (Il était une fois... Montréal-Nord, 2008)
Keywords: Clubs; Montréal-Nord; Parcs; Quartiers

Montréal, centre touristique - Samson, Marcel (Montréal 2001. Visages et défis d'une métropole, 1998)
Keywords: Tourisme

The Rise of the Cultural Marketplace - Lamonde, Yvan (Montreal: The History of A North American City, 2018)
Keywords: Bibliothèque centrale de Montréal; Carnaval; Cinéma; Hockey; Musique; Parc Sohmer; Saint-Laurent (rue); Théâtre; École littéraire de Montréal

Relations entre les activités sportives et les postes de budget au Service des sports de l'Université de Montréal pour 1977-1978 et 1978-1979 - Morin, Danielle (Université de Montréal, 1980)
Keywords: Université de Montréal

Paroisse Sainte-Gertrude - Lord, Claude (Il était une fois... Montréal-Nord, 2009)
Keywords: Montréal-Nord; Parcs; Quartiers

La décennie 1950... Suite. Paroisse Sainte-Gertrude - Lord, Claude (Il était une fois... Montréal-Nord, 2010)
Keywords: Montréal-Nord; Parcs; Quartiers

A Sporting Evolution: The Montreal Amateur Athletic Association, 1881-1981 - Morrow, Don (Amateur Athletic Association, 1981)
Keywords: Clubs; Montreal Amateur Athletic Association

Les débats publics suscités par la création des Expos de Montréal - Labelle, Christophe (Université de Montréal, 2015)
Keywords: Anglophones; Baseball; Expos de Montréal (Montreal Expos); Francophones; Nationalisme

The Royal Montreal Golf Club, 1873-1973; the Centennial of Golf in North America (s.é., 1973)
Keywords: Golf; Royal Montreal Golf Club

Chalet de la patinoire à Saint-Vital - Lord, Claude (Il était une fois... Montréal-Nord, 2009)
Keywords: Montréal-Nord; Parcs; Patin; Quartiers

The Royal Montreal Curling Club, 1807-1932 (s.é., 1932)
Keywords: Clubs; Curling; Royal Montreal Curling Club

The Montreal Snow Shoe Club, Its History and Record.. - Becket, Hugh W. (Becket Bros., 1882)
Keywords: Clubs; Montreal Snow Shoe Club; Raquetteurs

One Hundred and Fifty Years of Curling 1807-1957; The Royal Montreal Curling Club (s.é., 1957)
Keywords: Clubs; Curling; Royal Montreal Curling Club

La décennie 1950. Paroisse Sainte-Gertrude - Lord, Claude (Il était une fois... Montréal-Nord, 2009)
Keywords: Montréal-Nord; Parcs; Quartiers; Saint-Vital (paroisse)

Fête et société: le carnaval d'hiver à Montréal (1883-1889) - Dufresne, Sylvie (Montréal: activités, habitants, quartiers, 1984)
Keywords: Carnaval; Patin; Raquetteurs

La leçon de Montréal - Cohen, Jean-Louis; Sorkin, Michael; Lortie, André (Les années 60: Montréal voit grand, 2004)

Le sport parascolaire dans les écoles de la Commission des écoles catholiques de Montréal: émergence d'un réseau sportif dans le réseau d'enseignement public (1950-1970) - Montmarquette, Camille (Université du Québec à Montréal, 2018)
Keywords: Commission des écoles catholiques de Montréal

Album souvenir, Festival international de jazz de Montréal : 25 ans - Denis, Alain (Festival international de jazz de Montréal, 2004)
Keywords: Musicien; Musique

Montréal, ville touristique accessible? - Jolin, Louis; Sarrasin, Bruno (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Tourisme

Montréal: oasis gastronomique ou capitale culinaire? - Lemasson, Jean-Pierre (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Alimentation; Restaurant

Historique du Centre des loisirs des sourds de Montréal, 1901-1976: programme-souvenir (Centre des loisirs des sourds de Montréal, 1976)
Keywords: Centre de loisirs des sourds; Sourds

Learning from Montreal - Cohen, Jean-Louis; Sorkin, Michael; Lortie, André (The 60s: Montreal Thinks Big, 2004)

Horses, Hedges, and Hegemony: Foxhunting in the Countryside - Ingram, Darcy (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Clubs; Faune; Montreal Hunt Club

Attractions, curiosités, carnaval d'hiver, expositions agricoles et industrielles: le loisir public à Montréal au XIXe siècle - Dufresne, Sylvie (Montréal au XIXe siècle. Des gens, des idées, des arts, une ville, 1990)
Keywords: Carnaval; Expositions; Université McGill

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

My turn at bat : the sad saga of the Montreal Expos - Brochu, Claude (ECW Press, 2002)
Keywords: Expos de Montréal (Montreal Expos)

Formes et fonctions du loisir public à Montréal au XIXe siècle - Montpetit, Raymond; Dufresne, Sylvie (Travaux et conférences, 1975-1979, 1979)
Keywords: Théâtre

Naissance et affirmation de la culture commercialisée - Lamonde, Yvan (Histoire de Montréal et de sa région, 2012)
Keywords: Bibliothèque centrale de Montréal; Carnaval; Cinéma; Hockey; Musique; Parc Sohmer; Saint-Laurent (rue); Théâtre; École littéraire de Montréal

The Expos in Their Prime: The Short-Lived Glory of Montreal's Team, 1977-1984 - Usereau, Alain (McFarland, 2013)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Regards sur le troisième centenaire de Montréal - Robert, Mario (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Commémoration

Up, Up, and Away: The Kid, the Hawk, Rock, Vladi, Pedro, le Grand Orange, Youppi! The Crazy Business of Baseball, and the Ill-fated but Unforgettable Montreal Expos - Keri, Jonah (Random House Canada, 2014)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Il était une fois les Expos. Tome 1: Les années 1969-1984 - Doucet, Jacques; Robitaille, Marc (Hurtubise, 2009)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Il était une fois les Expos. Tome 2: Les années 1985-2004 - Doucet, Jacques; Robitaille, Marc (Hurtubise, 2011)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Sainte-Catherine Street: at the Heart of Montréal Life - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Keywords: Rues; Sainte-Catherine (rue)

Royal Montreal Golf Club, Dixie, P.Q (s.é., 1923)
Keywords: Golf; Royal Montreal Golf Club

SQUEEZE : représentations du baseball dans l'imaginaire social au Québec : 1994-2014 - Mineau, Francis (Université de Montréal, 2017)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

SQUEEZE. Représentations du baseball dans l'imaginaire social au Québec: 1994-2014 - Mineau, Francis (Université de Montréal, 2017)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Le Club des archères de Montréal existait-il réellement? - Martin, Gabriel (Histoire Québec, 2020)
Keywords: Clubs; Femmes; Histoire; Montreal Ladies Archery Club / Montreal Archery Club

The Establishment of an Institution: the Montreal Amateur Athletic Association 1881-1906 - Morrow, Don (Proceedings. Fourth Canadian Symposium on the History of Sport and Physical Education, 1979)
Keywords: Clubs; Montreal Amateur Athletic Association

The Powerhouse of Canadian Sport: the Montreal Amateur Athletic Association, Inception to 1909 - Morrow, Don (Journal of Sport History, 1981)
Keywords: Clubs; Montreal Amateur Athletic Association

Networks of Power: People and Positions at the Montreal Amateur Athletic Association during the Nineteenth Century - Morrow, Don (North American Society for Sport History - Proceedings and Newsletter, 1984)
Keywords: Clubs; Montreal Amateur Athletic Association

Les Expos: du parc Jarry au Stade olympique - Brodeur, Denis; Caza, Daniel (Éditions de l'Homme, 1996)
Keywords: Baseball; Expos de Montréal (Montreal Expos); Stade olympique

Baseball PQ: une histoire illustrée - de Foy, Marc (Les Éditions du Journal, 2019)
Keywords: Baseball; Expos de Montréal (Montreal Expos); Robinson, Jackie

The Influence of the Montreal Curling Club on the Development of Curling in the Canadas 1807-1857 - Simpson, Robert Wayne (Université Western Ontario, 1980)
Keywords: Clubs; Curling; Montreal Curling Club

The Montreal Parks and Playgrounds Association Inc. A Historical Study of the Association from the Year of Its Founding in 1896 to 1949 - Wilson, E. Laird (Université McGill, 1953)
Keywords: Montreal Parks and Playgrounds Association; Parcs

Keep on running: the YM-YWHA Wolf Pack - Regenstreif, Michael (YM-YWHA Montréal JCC, 2005)
Keywords: Course à pied

Maurice Richard et la presse sportive montréalaise : l'itinéraire d'une passion partisane, 1942-1955 - Lapointe, Étienne (Université du Québec à Montréal, 2019)
Keywords: Canadien (Club de hockey); Devoir (Le); Hockey; Montreal Gazette; Montreal Star; Montréal-Matin; Richard, Maurice; Émeutes

Chronique sportive ou politique? Le Canadien de Montréal et la crise constitutionnelle canadienne dans La Presse, Le Devoir et la Gazette (1976-1995). - Lemay, Clarence (Université d'Ottawa, 2020)
Keywords: Canadien (Club de hockey); Devoir (Le); Fédéralisme; Montreal Gazette; Nationalisme; Presse (La)

L'histoire et la culture comme leviers de développement urbain à Montréal - Bélanger, Anouk (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Histoire

Le goût des autres. Tamtams, Piknic Électronik et autres jeux de la sociabilité publique - Vernet, Laurent (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Mont-Royal (parc); Parcs; Places publiques; Île Sainte-Hélène

Le diable en ville: Alexandre Silvio et l'émergence de la modernité populaire au Québec - Lacasse, Germain; Massé, Johanne; Poirier, Bethsabée (Presses de l'Université de Montréal, 2012)
Keywords: Chanson; Cinéma

La conquête d'un espace public: les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Alcool

Des lieux d'appartenance: les bars gais des années 1950 - Higgins, Ross (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Alcool

Des Adonis en quête d'immortalité : la photographie homoérotique - Waugh, Thomas (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Photographie

Sulpician Retreats - Hubert, Ollivier (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Keywords: Communautés religieuses; Sulpiciens

Chroniques de l'école secondaire Henri-Bourassa. 1985: Année internationale de la Jeunesse - Blanchard, Nicole (Il était une fois... Montréal-Nord, 2019)
Keywords: Musicien; Musique; Étudiants

Chroniques de l'école secondaire Henri-Bourassa. Les années 80: je me souviendrai - Blanchard, Nicole (Il était une fois... Montréal-Nord, 2019)
Keywords: Enseignants; Étudiants

Si l'habitat St-Camille m'était conté - Pouliot, France (Il était une fois... Montréal-Nord, 2003)
Keywords: Églises

Parc Léonard - Lord, Claude (Il était une fois... Montréal-Nord, 2008)
Keywords: Clubs; Parcs; Patin

Guy Des Ormeaux. Réalisateur télévision - Pichette, Richard (Il était une fois... Montréal-Nord, 2009)
Keywords: Jeux olympiques; Radio-Canada; Télévision

Chroniques de l'école secondaire Henri-Bourassa. Devenir polyvalente - Blanchard, Nicole (Il était une fois... Montréal-Nord, 2018)
Keywords: Enseignement professionnel

Jackie Robinson...Un Américain à Villeray - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Baseball; Noirs; Villeray

Les lieux de villégiature - Hubert, Ollivier (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Scandale! Le Montréal illicite, 1940-1960 - Charlebois, Catherine; Lapointe, Mathieu (Les Éditions Cardinal, 2016)
Keywords: Criminalité; Photographie; Prostitution

Montréal : 25 ans de Formule 1 - Clairoux, Benoît (Hurtubise HMH, 2003)
Keywords: Automobile; Île Sainte-Hélène

Le football américain au Québec. Deuxième essai: les Castors de Montréal (Montreal Beavers), 1966-1967 - Veilleux, Denis (Denis Veilleux, 2013)
Keywords: Football

Montreal’s Francophone Hockey Beginnings, 1895-1910 - Vigneault, Michel (The Same but Different. Hockey in Quebec, 2017)
Keywords: Hockey

Étude patrimoniale du Parc olympique de Montréal - Vanlaethem, France; Bassil, Soraya; Munarim, Ulisses (Docomomo Québec, 2017)
Keywords: Jeux olympiques; Patrimoine; Stade olympique

Montréal football: un siècle et des poussières - Lemay, Daniel (Éditions La Presse, 2006)
Keywords: Football

The Montreal Maroons: The Forgotten Stanley Cup Champions - Brown, William (Véhicule Press, 1999)
Keywords: Hockey

Québec-Montréal: l'histoire d'une classique depuis 1931 - Langlois, Gaston (G. Langlois, 2002)
Keywords: Cyclisme

Sports et divertissements populaires à Montréal au XIXe siècle (s.é., 1976)

Jackie Robinson: une inoubliable saison de baseball à Montréal - Jedwab, Jack (Les Éditions Images, 1997)
Keywords: Baseball; Robinson, Jackie

La Pointe-aux-Trembles: aire de loisirs des Montréalais - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2006)
Keywords: Pointe-aux-Trembles; Quartiers

La Pointe-aux-Trembles: aire de loisirs des Montréalais - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2017)
Keywords: Pointe-aux-Trembles; Quartiers

Mises au jeu. Les sports féminins à Montréal, 1919-1961 - Detellier, Élise (Les éditions du remue-ménage, 2015)
Keywords: Femmes; Palestre nationale; Young Women's Christian Association (YWCA)

The "House of Hockey": Spatialized Memories of the Montreal Forum - Perrone, Julie (The Same but Different. Hockey in Quebec, 2017)
Keywords: Canadien (Club de hockey); Hockey

1906. L'ouverture du Ouimetoscope - Lacasse, Germain (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Cinéma

La Soirée du Hockey in Montreal: National Stakes in a Cultural War - Lapierre, Emmanuel (The Same but Different. Hockey in Quebec, 2017)
Keywords: Canadien (Club de hockey); Hockey

Hockey and Philanthropy: The Legacy of the Montreal Canadiens Children’s Foundation - Valois-Nadeau, Fannie (The Same but Different. Hockey in Quebec, 2017)
Keywords: Canadien (Club de hockey); Hochelaga

Coup franc: l'aventure du Concordia de Montréal, (1960 et 1961) - Veilleux, Denis; Prévost-Veilleux, Benoit (Denis Veilleux, 2018)
Keywords: Soccer

Étude patrimoniale du Parc olympique de Montréal - Édition actualisée et augmentée - Vanlaethem, France (Docomomo Québec, 2019)
Keywords: Jeux olympiques; Maisonneuve (quartier); Parcs; Patrimoine; Quartiers; Stade olympique

Toute l'histoire illustre et merveilleuse du Canadien de Montréal: Richard, Béliveau, Lafleur.. - Mouton, Claude (La Presse, 1986)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice

Le processus identitaire dans le soccer chez les italiens de Montréal - Spadari, Luigi (Université de Montréal, 1998)
Keywords: Italiens; Soccer

Baseball's Fabulous Montreal Royals:The minor league team that made major league history - Brown, William (R. Davies, 1996)
Keywords: Baseball; Robinson, Jackie

Les centres de loisirs: une étude sur les centres de loisirs de la ville de Montréal et Montréal-Nord, qui desservent une clientèle en majorité canadienne-française - Racette Cadieux, Rita (Université de Montréal, 1955)

Représentations et pratiques de la villégiature à Montréal au tournant du XXe siècle - Aubin-Des-Roches, Caroline (Université de Montréal, 2004)

Les Canadiens de Montréal vus par les fans: une exploration en trois temps - Sniec, Monika (Université de Montréal, 2004)
Keywords: Canadien (Club de hockey); Hockey

Une ville bien arrosée: Montréal durant l'ère de la prohibition (1920-1933) - Hawrysh, Michael (Université de Montréal, 2014)
Keywords: Alcool; Prohibition

La cinématographie-attraction à Montréal à la lumière de la législation (1896-1913) - Marzloff, Alice (Université de Montréal, 2016)
Keywords: Cinéma

Jackie Robinson, un été à Montréal: la fin de la ségrégation raciale dans le baseball - Dugas, Marcel (Hurtubise, 2019)
Keywords: Baseball; Noirs; Robinson, Jackie

Les rapports à la ville à travers les espaces de loisirs: Montréal, 1881-1940 - Shaffer, Valérie (Université de Montréal, 2009)
Keywords: Parcs; Places publiques; Réformistes

Ethnographie d'une pratique ludique urbaine: le skateboard sur la place Vauquelin à Montréal - Pégard, Olivier (Université de Montréal, 1996)
Keywords: Places publiques

The Depression Hockey League in Montreal, 1932-1960: Sport and Masculine Civic Performance before the Quiet Revolution - Holman, Andrew C. (The Same but Different. Hockey in Quebec, 2017)
Keywords: Hockey

De l'organisation au déroulement d'événements rave à Montréal: étude des mécanismes de régulation sociale - Maari, Frédéric (Université de Montréal, 2009)
Keywords: Danse; Musique

La relation politico-administrative au service des sports et loisirs de la ville de Montréal - Ringuette, Josée (Université de Montréal, 1997)

À toi pour toujours? Le Canadien de Montréal comme enjeu national d’une guerre culturelle - Lapierre, Emmanuel (Université de Montréal, 2011)
Keywords: Canadien (Club de hockey); Hockey; Nationalisme

L'évolution des musées accessibles au public à Montréal au XIXe siècle. Capitalisme culturel et représentations idéologiques - Gagnon, Hervé (Université de Montréal, 1995)
Keywords: Musées

La gestion des loisirs publics à Montréal: l'exemple du parc de l'île Sainte-Hélène, 1874-1914 - Desharnais, Josée (Université de Montréal, 1998)
Keywords: Parcs; Île Sainte-Hélène

« La force, la grâce, la souplesse »: l’éducation physique des jeunes filles canadiennes-françaises à Montréal (1860-1920) - St-Georges, Valérie (Université de Montréal, 2019)
Keywords: Femmes; Éducation physique

Fêtes et société au Québec: la visite du prince de Galles et la construction du Crystal Palace à Montréal, en 1860 - Montpetit, Raymond (Groupe de recherche en art populaire (GRAP), Travaux et conférences 1975-1979, 1979)
Keywords: Crystal Palace

Le carnet de bal. Objet précieux et capricieux pour l'histoire de la danse récréative à Montréal entre 1870 et 1940 - Roquigny, Peggy (À la recherche du savoir: Nouveaux échanges sur les collections du Musée McCord / Collecting Knowledge: New Dialogues on McCord Museum, 2016)
Keywords: Danse

Étude longitudinale des coureurs et coureuses inscrits au marathon international de Montréal: égalité d'accès et habitudes de vie - Gagné, Diane (Université de Montréal, 1985)

L’impact du loisir sur l’intégration sociale des minorités ethniques à Montréal: le cas des nouveaux arrivants originaires du Pérou - Murrugarra Cerna, Juan Carlos (Université de Montréal, 2010)
Keywords: Péruviens

Le parc Sohmer (1889-1919): un lieu majeur de culture populaire urbaine - Montpetit, Raymond (Cahier de la Société historique de Montréal, 1982)
Keywords: Parc Sohmer

Évaluation des bénéfices cardio-vasculaires associés à la consommation de poisson parmi les pêcheurs sportifs du Saint-Laurent de la région de Montréal - Godin, Catherine (Université de Montréal, 2000)

Sur la légèreté d'être gaie ou les constructions discursives du sport, du genre et de la sexualité chez les jeunes sportives de Montréal - Ravel, Barbara (Université de Montréal, 2006)

L'époque glorieuse des Expos - Usereau, Alain (Les Éditeurs réunis, 2009)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

L'extraordinaire saga de Nos Amours:1969-2004 - Keri, Jonah (Éditions au Carré, 2016)
Keywords: Baseball; Expos de Montréal (Montreal Expos)

Les loisirs paroissiaux, familiaux et scolaires: une étude sur les loisirs des membres de cent familles de la paroisse St-Charles de Montréal dans les milieux paroissial familial et scolaire durant cette année 1951 - Vincent, Cécile (Université de Montréal, 1951)
Keywords: Saint-Charles (paroisse)

Célébrer dans la tourmente: commémoration et exposition en milieu urbain - Bérubé, Harold (Montreal-Glasgow, 2005)
Keywords: Commémoration; Expositions

L'histoire avant et après de Queen of Angels Academy/The pre and post history of Queen of Angels Academy - Nieuwendyk, Dick (Héritage Dorval, 2021)
Keywords: Royal Montreal Golf Club

Guerre ou pas, j'irai danser la veille du jour de l'an. Chroniques d'une danseuse invétérée - Roquigny, Peggy (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Cabarets; Danse; Publicité

La Montagne vous appelle - Mathieu, Jocelyne (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Femmes; Mont Royal; Patin; Raquetteurs; Ski; Vêtements

Une journaliste du Bulletin à l'honneur. Gabrielle Roy remporte le prix Femina à Paris - des Rivières, Marie-José (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Quartiers; Roman; Saint-Henri

Alys vue par Rita - Savoie, Chantal (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Chanson; Musique; Radio

Pratiques cyclistes à Montréal, 1900-1950 - Beaulieu, Marion (Université du Québec à Montréal, 2017)
Keywords: Automobile; Cyclisme

"Montréal, ville de festivals" entre culture et tourisme culturel: le cas de Montréal en lumière - Simard, Émilie Julie (Université du Québec à Montréal, 2010)
Keywords: Tourisme

La rue Sainte-Catherine: au cœur de la vie montréalaise - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Keywords: Rues; Sainte-Catherine (rue)

Le Carnaval d'hiver de Montréal, 1883-1889 - Dufresne, Sylvie (Université du Québec à Montréal, 1980)
Keywords: Carnaval; Patin; Raquetteurs

Baseball, américanité et culture populaire histoire du baseball à Montréal: 1860-1914 - Coupal, Éric (Université du Québec à Montréal, 2001)
Keywords: Baseball

Le sport chez les Canadiens-français de Montréal au XIXe siècle - Janson, Gilles (Université du Québec à Montréal, 1993)
Keywords: Baseball; Crosse; Football; Palestre nationale; Raquetteurs

Pratiques inciviles et sentiment d'insécurité: une étude de cinq parcs montréalais - Léonard, Daniel (Université du Québec à Montréal, 2001)
Keywords: Parcs

Breaking à Montréal: ethnographie d'une danse de rue hip hop - Stevens, Lys (Université du Québec à Montréal, 2008)
Keywords: Danse

L'aménagement des parcs de voisinage, secteur Terrasse-Ontario: quartier Centre-Sud, Montréal - Béguier, Hélène (Université du Québec à Montréal, 2004)
Keywords: Centre-sud (quartier); Parcs; Quartiers

Étude de l'hivernité urbaine, analyse d'un récit de construction identitaire montréalais - Myriam, Guillemette (Université du Québec à Montréal, 2020)
Keywords: Carnaval; Climat; Espace souterrain

Les plaisirs de la danse à Montréal: transformation d'un divertissement et de ses pratiques - Roquigny, Peggy (Université du Québec à Montréal, 2012)
Keywords: Danse

Usages et représentations de l'espace public urbain dans le contexte du Festival International de Jazz de Montréal - Kammer, Eva (Université du Québec à Montréal, 2009)

Localisation industrielle et culture: une analyse comparative des districts de jeu électronique à Montréal et à Los Angeles - Pilon, Sylvianne (Université du Québec à Montréal, 2007)

Un regard sur les divertissements et les loisirs populaires à Montréal au XIXe siècle: culture, exotisme et commercialisation - Gagnon, Yvon (Université du Québec à Montréal, 2014)
Keywords: Parcs

Quand le cœur a ses raisons: analyse de la construction mythique du club de hockey le Canadien de Montréal - Valois-Nadeau, Fannie (Université du Québec à Montréal, 2009)
Keywords: Canadien (Club de hockey); Hockey

Les Foufounes Électriques: de l'underground à l'overground, étude de cas d'une sous-culture urbaine de Montréal - Palardy, Marianne (Université du Québec à Montréal, 2008)
Keywords: Alcool

Political Dimensions to Leisure and Cultural Activities in Canadian Cities, 1880-1940 - Dagenais, Michèle (Urban History, 1999)
Keywords: Bibliothèque centrale de Montréal; Jardin botanique

Le rôle des grands événements dans le développement touristique d'une destination métropolitaine: cas de la ville de Montréal 1960-1992 - Khomsi, Mohamed Reda (Université du Québec à Montréal, 2015)
Keywords: Expositions; Jeux olympiques; Tourisme

L'expérience de la pratique de la danse salsa des jeunes adultes dans deux discothèques latines de Montréal: une participation à une culture, une rencontre, un rituel - Burelle, Édith (Université du Québec à Montréal, 2001)
Keywords: Danse; Latino-Américains

Sports in Westmount (The Westmount Historian, 2012)
Keywords: Clubs; Golf; Hockey; Montreal Amateur Athletic Association; Patin; Royal Montreal Golf Club; École Selwyn House

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Wildlife, Conservation, and Conflict in Quebec, 1840-1914 - Ingram, Darcy (University of British Columbia Press, 2013)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Une histoire sociale du curling au Québec, de 1807 à 1980 - Richard, Pierre (Université du Québec à Trois-Rivières, 2006)
Keywords: Clubs; Curling; Femmes; Francophones; Montreal Curling Club

Le Plateau sur ses grands chevaux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
Keywords: Chasse à courre; Chevaux; Clubs; Montreal Hunt Club; Tramways; Transport en commun

La représentation des sports et des loisirs dans la presse montréalaise entre 1875 et 1890: la construction d'une identité canadienne - Plante, Mathieu (Université du Québec à Trois-Rivières, 2015)
Keywords: Canadian Illustrated News; Clubs; Crosse; Minerve (La); Montreal Witness; Nationalisme; Presse (La); Raquetteurs

La maison Nivard-De-Saint-Dizier au temps de John Crawford, haut lieu de chasse à courre - Tremblay Lamarche, Alex (Cap-aux-Diamants, 2020)
Keywords: Chasse à courre; Clubs; Crawford, John; Montreal Hunt Club; Nivard-De-Saint-Dizier (maison); Verdun

Montreal 1976 - Cayouette, Pierre (The Beaver, 2009)
Keywords: Jeux olympiques

Movie Palaces on Canadian Downtown Main Streets: Montreal, Toronto and Vancouver - Moore, Paul S. (Urban History Review / Revue d'histoire urbaine, 2004)
Les rues Sainte-Catherine à Montréal, Yonge à Toronto et Granville à Vancouver accueillent les premières salles de cinéma. À partir de 1896, les films sont présentés dans des lieux de divertissement variés. Lorsque les salles consacrées au cinéma apparaissent en 1906, elles sont édifiées çà et là, avant la délimitation nette au centre-ville d’un quartier réservé au cinéma. C’est vers 1920 que les théâtres de variétés, avec leurs primeurs cinématographiques, occupent une place prédominante quant à la fréquentation du cinéma en milieu urbain, position qu’ils conservent jusque dans les années 1950. Après avoir exposé brièvement la manière dont a pris forme la fréquentation des salles de cinéma, l’article traite de la proximité entre les salles du centre-ville et le plus grand magasin de chaque ville. Vient ensuite une analyse théorique portant sur la manière dont le divertissement et la consommation donnent un sens au fait d’être au « cœur de la ville » dans le quotidien en milieu urbain. Les marquises des salles de cinéma renouvellent l’utilisation sociale de l’éclairage électrique et du divertissement urbain, et deviennent ainsi un symbole de l’organisation des foules et des consommateurs du centre-ville en grand public attentif. La conclusion offre un bref exposé du déclin des salles de cinéma, des années 1970 à l’année 2000, et présente les conséquences de leur remplacement par les complexes cinématographiques, soit leur démolition ou leur préservation.
Keywords: Cinéma

Montréal vernaculaire/Montréal spectaculaire: dialectique de l’imaginaire urbain - Bélanger, Anouk (Sociologie et sociétés, 2005)
Keywords: Quartiers; Saint-Laurent (quartier)

Leisure Facilities in Montreal 1970 - Acosta, Carlos A. (Université McGill, 1972)

The Montreal Canadians: A Hockey Dynasty - Mouton, Claude (Van Nostrand Reinhold, 1980)
Keywords: Canadien (Club de hockey); Hockey

Jackie Robinson as a Montreal Royal - Frommer, Harvey (Proceedings. 5th Canadian Symposium of the History of Sport and Physical Education, 1982)
Keywords: Baseball; Robinson, Jackie

The Montreal Canadiens: a Hockey Metaphor - Herlan, James J. (Quebec Studies, 1983)
Keywords: Canadien (Club de hockey); Hockey

The Montréal First Nine: a Study of English Language Newspaper Coverage of Baseball in Nineteenth Century Montréal - Braganza, Paul Michael Henry (Université Concordia, 2006)
Keywords: Baseball

Sam Pollock et le Canadien de Montréal - Bonneau, Line; Hafsi, Taïeb (Presses de l'Université du Québec, 1996)
Keywords: Canadien (Club de hockey); Hockey

Un Vauxhall à Montréal au XVIIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1927)

Vice et corruption à Montréal, 1892-1970 - Brodeur, Magaly (Presses de l'Université du Québec, 2011)
Keywords: Alcool; Criminalité; Police

1883-1889: quand Montréal avait son carnaval! - Dufresne, Sylvie (Cap-aux-Diamants, 2001)
Keywords: Carnaval; Patin; Raquetteurs

Le Jardin botanique de Montréal: une responsabilité municipale? - Dagenais, Michèle (Revue d'histoire de l'Amérique française, 1998)
Keywords: Jardin botanique

Montréal 1917: L'émergence d'une identité patrimoniale - Joly, Diane (Patrimoine et patrimonialisation: du Québec et d'ailleurs, 2006)
Keywords: Commémoration; Patrimoine

La diffusion du hockey à Montréal 1895-1910 - Vigneault, Michel (Canadian Journal of the History of Sport / Revue canadienne de l'histoire des sports, 1986)
Keywords: Hockey

Les Canadiens de Montréal: une dynastie du hockey - Mouton, Claude (Van Nostrand Reinhold, 1981)
Keywords: Canadien (Club de hockey); Hockey

Working-Class Physical Recreation in Montreal, 1860-1895 - Metcalfe, Alan (Working Papers in the Sociological Study for Sports and Leisure, 1978)
Keywords: Éducation physique

Beyond the Decline: Revaluing Montreal's Movie Palaces - Heather Gibb, Alexandra (Université McGill, 2015)
Keywords: Cinéma; Conservation; Patrimoine

Le Carnaval d'hiver de Montréal, 1883-1889 - Dufresne, Sylvie (Urban History Review / Revue d'histoire urbaine, 1983)
Keywords: Carnaval; Patin; Raquetteurs

The British Garrison and Montreal Society, 1830-1850 - Vineberg, Robert (Canadian Military History, 2012)
Keywords: Armée; Britanniques; Garnison

Dissipating Darkness: Governing Nighttime in Montreal, 1954-1986 - Caron, Matthieu (Université de Toronto, 2023)
Keywords: Criminalité; Drapeau, Jean; Prostitution

« A Profusion of Light » in Nineteenth-Century Montreal - Olson, Sherry (Espace et culture, 1995)
Keywords: Patrie (La); Presse (La)

1917: une première célébration de la fondation de Montréal - Lacroix, Laurier (Les Cahiers des Dix, 2016)

Loisir public et société à Montréal au XIXe siècle - Montpetit, Raymond (Loisir et Société / Society and Leisure, 1979)

The Cultural Diffusion of Hockey in Montreal, 1890-1910 - Vigneault, Michel (Université de Windsor, 1986)
Keywords: Hockey

Five-Wagon Hockey; The Story of the Montreal Canadiens - O'Brien, Andy (Ryerson Press, 1967)
Keywords: Canadien (Club de hockey); Hockey

Medias et société: le cinéma à Montréal, 1896-1929 - Mondoux, André (Université Laval, 1984)
Keywords: Cinéma

Organized Sport and Social Stratification in Montreal: 1840-1901 - Metcalfe, Alan (Canadian Sport Sociological Perspectives, 1976)

L'escrime et les métiers d'armes à Montréal - Massicotte, E.-Z. (Bulletin des recherches historiques, 1923)
Keywords: Armuriers

A Recreational Hinterland Comparison between Montréal and Québec City - Secondi, Bruno (Université McGill, 1990)

The Role and Functions of the Tavern in Montreal - Jupp, George Alexander (Université de Calgary, 1969)
Keywords: Alcool

Beyond Eden: Cultivating Spectacle in the Montreal Botanical Garden - Armstrong, Ann (Université Concordia, 1997)
Keywords: Jardin botanique; Marie-Victorin, Frère

Embodying Nation: Indigenous Sports in Victorian Montreal, 1860-1885 - Poulter, Gillian (Contesting Bodies and Nation in Canadian History, 2013)
Keywords: Autochtones; Nationalisme

Le Parc Jarry de Montréal. 75 ans d'histoire - Hudon, François (Les Éditions Logiques, 2001)
Keywords: Parcs

The Montreal Canadiens: An Illustrated History of a Hockey Dynasty - Mouton, Claude (Key Porter Books, 1987)
Keywords: Canadien (Club de hockey); Hockey

Divertir et instruire: les musées de Montréal au XIXe siècle - Gagnon, Hervé (G.G.C., 1999)
Keywords: Musées

The Little Man of Iron: the 1902 Montreal Hockey Club - Morrow, Don (Revue canadienne de l'histoire des sports / Canadian Journal of History of Sport, 1981)
Keywords: Hockey

The Evolution of Organized Physical Recreation in Montreal, 1840-1895 - Metcalfe, Alan (Histoire sociale / Social History, 1978)
Keywords: Éducation physique

La Place des Arts et la vie nocturne à Montréal - Straw, Will (50 ans de la Place des Arts, 2015)
Keywords: Place des Arts; Places publiques

Le jeu de la crosse à Montréal au XIXe siècle - Ferland, Daniel (Patrimoine, 2008)
Keywords: Autochtones; Crosse

Le parc olympique de Montréal à la croisée d'ambitions impérieuses - Vanlaethem, France (ARQ - Architecture & Design Québec, 2022)
Keywords: Jeux olympiques; Parcs; Stade olympique

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord, Gwen; Lord, Richard; Noirs; Robinson, Jackie

'Returning to nature': Vacation and Life Style in the Montreal Region - Dagenais, Michèle (Resources of the City: Contributions to an Environmental History of Modern Europe, 2005)

Salsa and its Transnational Moves: The Commodification of Latin Dance in Montreal - Pietrobruno, Sheenagh (Université McGill, 2001)
Keywords: Danse

Les chars de Longueuil pour la Saint-Jean-Baptiste à Montréal - Millette, Charles-Édouard (Société d'histoire de Longueuil, 1974)
Keywords: Longueuil; Saint-Jean-Baptiste (fête)

The Neighbourhood Movie House in Montreal, 1925-1929: The Harmonius World - Kolomeir, Harriet T. (Université Concordia, 1987)
Keywords: Cinéma

Le parc Sohmer de Montréal, 1889-1919. Un lieu de culture urbaine - Lamonde, Yvan; Montpetit, Raymond (Institut québécois de recherche sur la culture, 1986)
Keywords: Parc Sohmer

Imagining the City of Festivals: Festivalization and Urban Space in Montréal - Macdonald, Amy (Université McGill, 2012)
Keywords: Tourisme

The Twentieth Century Bible - Listening to the Radio in Montreal, 1924-39 - Brand, Paul (The Register, 1980)
Keywords: Radio

Montréal, un haut-lieu de la lutte au début du XXe siècle - Janson, Gilles (Cap-aux-Diamants, 2002)

Montreal Movies Palaces. Great Theatres of the Golden Era, 1884-1938 - Lanken, Dane (Archives of Canadian Art (& Design), 1993)
Keywords: Cinéma

A Study of Recreation in a Rapidly Developing Community in Montreal - Faughnan, Jeanne; Gabois, Denise; Miller, Robert; Ozier, Morris; Romer, Gabrielle; Sinuk, Morris (Université McGill, 1953)
Keywords: Quartiers; Saint-Laurent (quartier)

D’un stade mal-aimé à un stade oublié: l’Autostade de Montréal - Gaudette, Marilyne; Roult, Romain; Reda Khomsi, Mohamed; Lefebvre, Sylvain (Urban History Review / Revue d'histoire urbaine, 2017)
Keywords: Expositions; Jeux olympiques; Stade olympique

De Montmartre à Broadway: le cabaret Au matou botté de Montréal (1929-1932) - Bellemare, Luc (Mens, 2015)
Keywords: Cabarets; Cafés

Domesticating Parks and Mastering Playgrounds: Sexuality, Power and Place in Montreal, 1870-1930 - Schmidt, Sarah (Université McGill, 1997)
Keywords: Délinquance; Mont-Royal (parc); Parcs; Places publiques

Fuir la ville: villégiature et villégiateurs dans la région de Montréal, 1890-1940 - Dagenais, Michèle (Revue d'histoire de l'Amérique française, 2005)

L'Affaire Richard: A Situational Analysis of the Montreal Hockey Riot of 1955 - Duperreault, Jean-Raymond (Revue canadienne de l'histoire des sports / Canadian Journal of History of Sport, 1981)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice; Émeutes

Homonormative Architecture & Queer Space: The Evolution of Gay Bars and Clubs in Montréal - Vallerand, Olivier (Université McGill, 2010)
Keywords: Alcool

''A City of Sin No More'': Sanitizing Montreal in Print Culture, 1964-71 - Straw, Will (International Journal of Canadian Studies / Revue internationale d'études canadiennes, 2014)
Keywords: Tourisme

Montréal à l’heure du jubilé de diamant de la reine Victoria (1897) - Tremblay Lamarche, Alex (Cap-aux-Diamants, 2017)

Le sport au Canada français au 19e siècle: le cas de Montréal, 1800-1914 - Metcalfe, Alan (Loisir et Société / Society and Leisure, 1983)

The Loveliest Lake in the New Dominion: Montreal villégiateurs on Lake Memphremagog, 1860-1914 - Robinson, Jody (Université de Sherbrooke, 2012)

Divertissement et patriotisme: la genèse des musées d'histoire à Montréal au XIXe siècle - Gagnon, Hervé (Revue d'histoire de l'Amérique française, 1995)
Keywords: Musées

La renaissance d'un sport organisé au Canada: le hockey à Montréal, 1875-1917 - Vigneault, Michel (Université Laval, 2001)
Keywords: Canadien (Club de hockey); Hockey

Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
Keywords: Alcool

Stratégies identitaires et loisirs sportifs de groupe de récents immigrants chinois de première génération à Montréal - Zhang, Dan (Université du Québec à Trois-Rivières, 2007)
Keywords: Chinois

Culture et exotisme: les panoramas itinérants et le jardin Guilbault à Montréal au XIXe siècle - Montpetit, Raymond (Loisir et Société / Society and Leisure, 1983)
Keywords: Jardin Guilbault; Jardins; Peinture

Retrouver la ville à la campagne: la villégiature à Montréal au tournant du XXe siècle - Aubin-Des-Roches, Caroline (Urban History Review / Revue d'histoire urbaine, 2006)

Entre tradition et modernité. Espaces et temps de loisirs à Montréal et Toronto au XXe siècle - Dagenais, Michèle (Canadian Historical Review, 2001)
Keywords: Mont-Royal (parc); Parcs; Tramways; Transport en commun

Les méga-plexes cinématographiques et le nouvel environnement périurbain de la région métropolitaine de Montréal - Sénécal, Gilles (Géographies et Cultures, 2005)
Keywords: Cinéma

Gone to the Dogs: An Ethnography of Breeding and Rearing Registered Dogs within the Montreal Area - Aro, Judoth (Université Concordia, 2003)

The Montreal Forum : The Hockey Arena at the Nexus of Sport, Religion, and Cultural Politics - Shubert, Howard (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l'étude de l'architecture au Canada, 2011)
Keywords: Canadien (Club de hockey); Hockey

Un haut lieu de la culture populaire à Montréal au XIXe siècle: le Jardin Guilbault - Gaudet, Sylvain (Cap-aux-Diamants, 2009)
Keywords: Jardin Guilbault; Jardins

Passage obligé: les réseaux de correspondance dans la constitution de collections particulières à Montréal, 1870-1910 - Truchon, Caroline (Cahiers d'histoire, 2012)
Keywords: Numismatie

Becoming Native in a Foreign Land: Sport, Visual Culture and Identity in Montreal, 1840-85 - Poulter, Gillian (University of British Columbia Press, 2009)
Keywords: Autochtones; Britanniques; Français

À l’assaut de Montréal: les chanteurs country-western dans les studios de la métropole, 1942-1958 - Lefrançois, Catherine (Mens, 2015)
Keywords: Chanson; Musicien; Musique

Des espaces aux pratiques de récréation: la régulation des loisirs publics à Montréal et Toronto, 1870-1940 - Dagenais, Michèle (La régulation sociale entre l’acteur et l’institution. Pour une problématique historique de l’interaction / Agency and Institutions in Social Regulation: Towards an Historical Understanding of Their Interaction, 2005)
Keywords: Parcs; Places publiques

Nationalisme culturel et performance dans l'histoire du Canadien de Montréal (1926-2012). Une étude de cas - Lapierre, Emmanuel (Globe: revue internationale d'études québécoises, 2012)
Keywords: Canadien (Club de hockey); Hockey; Nationalisme

''Une grande fête canadienne'': les Autochtones et le programme Arts et culture des Jeux olympiques de Montréal - Bureau-Capuano, Mélissa (Les Cahiers d'histoire, 2016)
Keywords: Autochtones

Le base-ball est mort, vive le soccer!: les années de gloire du soccer montréalais, 1949-1965 - Morelli, Joseph (Zio, 2003)
Keywords: Soccer

Les gens de Montréal à l'époque de la Confédération: illustrations et textes de L'Opinion publique - Deschênes, Gaston (Septentrion, 2017)
Keywords: Gravure; Opinion publique (L')

Inscrire le pouvoir municipal dans l’espace urbain: les réseaux des parcs à Montréal et Toronto, 1870-1940 - Dagenais, Michèle (The Canadian Geographer / Le Géographe canadien, 2002)
Keywords: Parcs

Une oasis de plaisirs en Amérique du Nord. Montréal et l'industrie du divertissement des années 1920-1950 - Bélanger, Anouk; Sumner, Lisa (La ville autrement, 2005)
Keywords: Alcool; Cabarets; Prohibition

"Flachaire a atterri trois fois" – Le séjour à Montréal d'un pilote de chasse français en juin 1918 - Fortier, Rénald (Histoire Québec, 2015)
Keywords: Avionnerie; Guerre

Lorsque sport, politique et culture se rencontrent : les combats des politiciens nationalistes lors des Jeux olympiques de Montréal - Plante, Benjamin (Histoire Québec, 2024)
Keywords: Jeux olympiques; Nationalisme

La danse pour tout un chacun: pratiques différenciées d’un loisir commercial à Montréal pendant l’entre-deux-guerres - Roquigny, Peggy (Mens, 2015)
Keywords: Danse

Les rapports entre Autochtones et Blancs dans le sport de la crosse de la région de Montréal au XIXe siècle - Ferland, Daniel (Université de Sherbrooke, 2007)
Keywords: Autochtones; Crosse

The British Army and Sport in Canada: Case Studies of the Garrison of Halifax, Montreal and Kingston to 1871 - Day, Robert Douglas (Université d'Alberta, 1981)
Keywords: Armée; Britanniques; Garnison

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Becoming Native in a Foreign Land: Visual Culture, Sport, and Spectacle in the Construction of National Identity in Montreal, 1840-1885 - Poulter, Gillian (York University, 1999)
Keywords: Autochtones; Britanniques; Français

A captivating ''Open City'': the production of Montreal as a ''wide-open-town'' and ''ville ouverte'' in the 1940s and '50s - Kuplowsky, Adam (Université McGill, 2014)
Keywords: Alcool; Criminalité; Délinquance; Prostitution

Les espaces verts de Montréal à la fin du XIXe siècle et au début du XXe siècle: le cas du parc Lafontaine - Héraut, Mariette (Université Michel de Montaigne-Bordeaux 3, 2001)
Keywords: Parc La Fontaine; Parcs

Patrimoine paysager et transaction sociale: le cas des parcs du Mont-Royal à Montréal et d'El Paseo del Bosque à la Plata - Contin, Mabel Irma (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2012)
Keywords: Mont-Royal (parc); Parcs; Patrimoine; Paysages

La ville de Montréal et la question des jeux de hasard et d'argent (1930-1970): crime organisé, corruption et financement municipal - Brodeur, Magaly (Université de Sherbrooke, 2008)
Keywords: Alcool; Criminalité; Police

De la mode au bon vieux temps? Paramètres du maintien de danses des dernières décennies du XIXe siècle dans le Montréal de l'entre-deux-guerres - Roquigny, Peggy (Bulletin Mnémo, 2015)
Keywords: Danse

Évolution des programmations et de l'écoute de deux stations de télévision francophones dans la région centrale de Montréal de 1959 à 1965: les cas de CBFT et CFTM-TV - Vézina, François (Université Laval, 1987)
Keywords: Télévision

Bois urbain et controverses locales, ou comment intégrer la nature à la ville - Sénécal, Gilles; Saint-Laurent, Diane (Québec 2002. Annuaire politique, social, économique et culturel, 2001)
Keywords: Conservation

Les nuits de la «Main»: cent ans de spectacles sur le boulevard Saint-Laurent, 1891-1991 - Bourassa, André-G.; Larrue, Jean-Marc (VLB, 1993)
Keywords: Rues; Saint-Laurent (rue)

Dow présente l'épopée des Canadiens, de Georges Vézina à Maurice Richard 46 ans d'histoire, 1909-1955 - Mayer, Charles (Brasserie Dow, 1956)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice; Vézina, Georges

Les Ouimetoscopes. Léo-Ernest Ouimet et les débuts du cinéma québécois - Bélanger, Léon-H. (VLB Éditeur, 1978)
Keywords: Cinéma; Ouimet, Léo-Ernest

Record of Winter Sports. 1883-1884 - Becket, Hugh W. (Becket Bros, 1884)

Histoire de Jos. Montferrand, l'athlète canadien - Sulte, Benjamin (Beauchemin, 1899)
Keywords: Montferrand, Joseph

Jos. Montferrand - Sulte, Benjamin (s.é., 1924)
Keywords: Montferrand, Joseph

Jean Béliveau: une époque, un regard - Béliveau, Jean; Goyens, Chrys; Turowetz, Allan (Art Global et Libre Expression, 1994)
Keywords: Canadien (Club de hockey); Hockey

Emparons-nous du sport: les Canadiens français et le sport au XIXe siècle - Janson, Gilles (Guérin, 1995)
Keywords: Francophones

Jean Béliveau: ma vie bleu-blanc-rouge - Béliveau, Jean; Goyens, Chrys; Turowetz, Allan (Hurtubise HMH, 2005)
Keywords: Canadien (Club de hockey); Hockey

Les yeux de Maurice Richard: une histoire culturelle - Melançon, Benoît (Fides, 2012)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice

Jean Béliveau: un grand Canadien - Bertrand, Luc (Célébrités / Collection biographique, 2001)
Keywords: Canadien (Club de hockey); Hockey

Maurice Richard - Forest, Michel (Célébrités canadiennes, 1991)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice

À l'affiche dans le Sud-Ouest... - Labrosse, Richard; Racine, Yolande (Collection de la Société d'histoire de Pointe-Saint-Charles, 2013)
Keywords: Cinéma; Côte-Saint-Paul; Griffintown; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Saint-Henri; Sainte-Cunégonde; Ville Émard

La glorieuse histoire des Canadiens - Bruneau, Pierre; Léandre, Normand (Éditions de l'Homme, 2003)
Keywords: Canadien (Club de hockey); Hockey

Allons aux régates de la Pointe-aux-Trembles, 1958-1971 - Lebeuf, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2019)
Keywords: Navigation; Pointe-aux-Trembles

Une relation orageuse au cinéma - Lever, Yves (Le Devoir: un siècle québécois, 2010)
Keywords: Cinéma; Devoir (Le)

Emmène-nous à La Ronde: 50 ans de plaisirs forains - Demers, Tristan (Éditions de l'Homme, 2017)
Keywords: Expositions

Désir(s) de vertige: 25 ans d'audace - Jacob, Pascal; Vézina, Michel (École nationale de cirque et Les 400 coups, 2007)
Keywords: Cirque; École nationale de cirque

The Royal St. Lawrence Yacht Club, 1888-1988 - Hanson, E. George (Royal St. Lawrence Yacht Club, 1988)
Keywords: Clubs; Navigation; Royal St. Lawrence Yacht Club

Le Domaine. Une belle histoire qui se poursuit... Les loisirs du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc., 2005)
Keywords: Domaine Saint-Sulpice; La Familiale; Logement

Red mitten nationalism: sport, commercialism, and settler colonialism in Canada - Fresco, Estée (McGill-Queen's University Press, 2022)
Keywords: Autochtones; Jeux olympiques; Nationalisme

Le Festival Mondial de l'Expo 67: un éblouissement à l'origine de la fondation de l'Opéra du Québec? - Lapierre, David (Université de Montréal, 2006)
Keywords: Opéra

La nouvelle danse montréalaise: ses antécédents, ses perceptions publiques, ses caractéristiques: un essai de définition - Tembeck, Iro Valaskakis (Université de Montréal, 1994)
Keywords: Danse

"They always Remain Girls": La re/production des rapports de genre dans les sports féminins au Québec, 1919-1961 - Detellier, Élise (Université de Montréal, 2011)
Keywords: Femmes

Genre et pouvoir: relation entre danseurs nus et clientèle féminine et masculine - Robillard, Julie (Université de Montréal, 2011)
Keywords: Danse

The Mobility and Embodiment of Modern Yoga - Salvatore, Vanessa (Université de Montréal, 2013)

Évolution de l'image projetée par le Club de Hockey Canadien depuis ses origines jusqu'au mythe de la tradition glorieuse - Black, François (Université de Montréal, 1992)
Keywords: Canadien (Club de hockey); Hockey

«En vacances...en voiture...en Pontiac!» Les représentations de genre à travers les loisirs dans La Revue moderne et Châtelaine, 1945-1969 - Bergeron, Caroline (Université de Montréal, 2014)
Keywords: Revue moderne (La)

La métabolisation des Jeux Olympiques : capacité transformative et héritage des méga-événements dans le paysage urbain. - Zarzani, Alessia (Université de Montréal, 2017)
Keywords: Jeux olympiques; Paysages

« Who in hell are the McGill co-eds? A girls’ team you say? » : les enjeux reliés aux rapports genrés entourant le hockey féminin à McGill (1894—1941) - Scaire, Jérémy (Université de Montréal, 2024)
Keywords: Femmes; Hockey; Université McGill

Du divertissement à l'institution de sens: pour une compréhension du phénomène du clubbing commercial - Langlais-Blais, Jean-Philippe (Université du Québec à Montréal, 2011)
Keywords: Alcool

Mémoire et histoire: le processus d’héroïsation du Rocket - Perrone, Julie (Université du Québec à Montréal, 2007)
Keywords: Commémoration; Hockey

La petite reine et les femmes: la bicyclette au Québec, 1880-1920 - Gagné, Amélie (Université du Québec à Montréal, 2004)
Keywords: Cyclisme; Femmes

Le sport et l’identité collective au Canada: la série du siècle de 1972 - Beauchamp, Pierre-Luc (Université du Québec à Montréal, 2005)
Keywords: Hockey

Halte-là le Canadien est là: analyse socio-sporto-culturelle de la série Bleu-Blanc-Rouge (1969-1979) de Serge Lemoyne (1941-1998) - Fortier, Nadège (Université du Québec à Montréal, 2013)
Keywords: Canadien (Club de hockey); Hockey

Maurice Richard et la presse sportive montréalaise: l'itinéraire d'une passion partisane, 1942-1955 - Lapointe, Étienne (Université du Québec à Montréal, 2019)
Keywords: Canadien (Club de hockey); Hockey; Richard, Maurice; Émeutes

Jeunes femmes et loisirs commerciaux durant les années folles (1919-1929): Étude des discours ecclésiastiques et journalistiques - Comtois, Patricia (Université du Québec à Montréal, 2007)
Keywords: Femmes; Patin; Ski